Understanding the role of soot oxidation in gasoline combustion: A numerical study on the effects of oxygen enrichment on particulate mass and number emissions in a spark-ignition engine. (15th March 2019) - Distaso, E.; Amirante, R.; Tamburrano, P.; Reitz, R.D.
Highlights: The study presents results concerning soot formation and oxidation mechanics. Pure O2 addition to gasoline avoided the uncertainties of oxygenated-fuel chemistry models. Thorough 3-D CFD simulations were compared with existing experimental measurements. Oxygen addition increased the production rates of both OH radicals and soot precursor species. Abstract: The production of increasingly clean engines has become imperative. More stringent regulations for internal combustion engines are constantly proposed, and recent number-based regulations have become a new challenge, since historically only a mass-based regulation needed to be met. It is known that soot particles detectable at the exhaust of an engine are the results of the competition between the formation of soot precursor species and their oxidation. However, the attention is mainly focused on inhibiting soot precursors formation, and much less research is dedicated at elucidating the benefits achievable from enhancing soot oxidation rates. Soot oxidation can be enhanced by increasing the in-cylinder oxygen content. Oxygenated fuels, which are often added to gasoline in order to achieve more efficient combustion, can represent a possible way in the pursuit of this goal. However, chemical mechanisms are still uncertain for practical fuels, and ambiguous results can be produced when the effect of oxygenated fuels on gasoline engine combustion and soot emissions is considered. In the present study, 3-D Computational Fluid Dynamics simulations were performed and the numerical results were compared with existing experimental data, in which load increases were achieved by pure oxygen addition within the intake manifold of a single-cylinder Spark-Ignition (SI) engine. Studying the effects that an addition of 5% and 10% by volume (with respect to air) of additional oxygen produces on the combustion process, allowed to provide basic additional information on soot formation and oxidation, avoiding the uncertainties associated with chemistry models. A semi-detailed soot model and a chemical kinetic model, including poly-aromatic hydrocarbon formation, were coupled with the G-equation flame propagation model for the SI engine simulations and for predicting soot mass and particulate number density. Improvements in the modeling of gasoline premixed combustion were achieved, as well. Specifically, different approaches in the evaluation of the laminar flame speed of gasoline (which is a key factor for obtaining reliable SI engine simulations) were critically compared and analyzed. The numerical results showed aspects that were not possible to appreciate by only referring to the experimental results on which this work was based. It was possible to observe that the higher soot concentrations were located in regions characterized by lower temperatures and lower OH concentrations. Oxygen addition favored a faster burning velocity and produced higher in-cylinder temperatures. However, the production rates of both OH radicals and soot precursor species resulted enhanced. The analysis of these concurrent phenomena allowed to explain why in the experiments the soot mass per kg of fuel was lower for the oxygenated combustion cases.